Glass composition, crystallized glass, and its manufacturing method and use
A tailored glass composition and crystallization process for crystallized glass, focusing on controlled ratios of SiO2, Al2O3, P2O5, Li2O, Na2O, and ZrO2, addresses the high haze and b value issues, resulting in improved mechanical strength and transparency for electronic device protection.
Patent Information
- Application Number
- JP2024540041
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-31
- Filing Date
- 2022-12-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-14
AI Technical Summary
Conventional crystallized glass exhibits high haze and large b value, affecting its transmittance and usability due to issues in the manufacturing process such as agglomeration of glass composition and interface morphology of crystal grains.
A specific glass composition comprising SiO2, Al2O3, P2O5, Li2O, Na2O, and ZrO2, with controlled ratios and addition of B2O3 and/or CaO, combined with a crystallization process to form lithium disilicate and petalite phases, is used to produce crystallized glass with reduced haze and improved mechanical properties.
The proposed glass composition significantly reduces haze and b value, enhancing the mechanical strength and transparency of the crystallized glass, making it suitable for protective applications in electronic devices.
Smart Images

Figure 2024545924000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Chinese patent application having application number 202111682724.5, filed on December 31, 2021, Chinese patent application having application number 202111681556.8, filed on December 31, 2021, and Chinese patent application having application number 202111682722.6, filed on December 31, 2021, the entire contents of which are incorporated herein by reference.
[0002] Technical Field This application relates to the field of glass making technology, and in particular to glass compositions, crystallized glasses and their methods of manufacture and use. [Background technology]
[0003] With the development of display technology, glass is commonly used to protect display devices. The cover glass for protecting electronic products on the market generally belongs to high alumina silicate glass. High alumina is advantageous for improving the stress strength and stress layer depth after ion exchange, but the drop resistance of glass is poor. Some studies have shown that 70% of electronic product breakages are caused by careless drops.
[0004] By introducing a nucleating agent into the glass recipe or adjusting the compounding ratio composition of oxides in the recipe, one or more crystalline phases called crystallized glass are formed in the subsequent heat treatment process. Since it not only has the high transparency of glass but also the high strength of ceramics, it can improve the average hardness, fracture toughness, and other performance of glass. The microcrystalline phase in crystallized glass can block the propagation path of microcracks, which is favorable for the overall improvement of the scratch resistance, impact resistance, drop resistance, and other performance of glass.
[0005] The performance of crystallized glass is determined by the ratio of the crystal phase to the glass phase, the size of the crystal grains, etc. During the manufacturing process of crystallized glass, due to factors such as the aggregation of the glass composition, the interface form of the crystal phase, and the external form of the crystal grains, currently manufactured transparent crystallized glass has a large b value, high haze, and macroscopically transmits light with a yellowish tinge, which affects the transmittance and usage performance of the crystallized glass. Summary of the Invention [Problem to be solved by the invention]
[0006] The main object of the present application is to provide a glass composition, a crystallized glass, and a manufacturing method and use thereof, in order to solve the problems of high b value and high haze of conventional crystallized glass. [Means for solving the problem]
[0007] In order to achieve the above object, the present application provides, in mass %, 71.5-74.5% SiO2, 6.2-8.7% Al2O3, 1.7-3% P2O5, 10-12.5% LiO, 0.1-2% Na2O, and A glass composition is provided that contains 3-5% ZrO2.
[0008] In one embodiment, it further contains 0.1-1.7% B2O3 and / or 0.1-1.5% CaO.
[0009] In one embodiment, −1.1≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦6.7.
[0010] In one embodiment, 0.19≦[W(LiO)−W(AlO)] / [W(PO)+W(ZrO)]≦0.98.
[0011] In one embodiment, 0.06≦[W(ZrO2)−3×W(B2O3)] / W(P2O5)≦1.57.
[0012] In one embodiment, in weight percent: 72-74% SiO2, 7.5-8.4% Al2O3, 2-2.8% P2O5, 0.3-0.8% B2O3, 10.5-11.8% LiO, 0.5-1.3% Na2O, and Contains 3.4-4.7% ZrO2.
[0013] In one embodiment, 0.6≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦5.4; 0.28≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.8, 0.5≦[W(ZrO2)-3×W(B2O3)] / W(P2O5)≦1.36.
[0014] In one embodiment, in weight percent: 72.5-73.5% SiO2, 7.7-8% Al2O3, 2.1-2.5% P2O5, 0.5-0.7% B2O3, 11-11.5% LiO, 0.7-1.1% Na2O, and Contains 3.8-4.4% ZrO2.
[0015] In one embodiment, 2.5≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦4.3; 0.43≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.64, 0.81≦[W(ZrO2)-3×W(B2O3)] / W(P2O5)≦1.16.
[0016] The present application provides a glass composition comprising, in mass%, 72-74.3% SiO2, 7-8.5% Al2O3, 1.8-3% P2O5, 10.2-12.5% Li2O, 0.5-2% Na2O, and 3.5-4.7% ZrO2.
[0017] In one embodiment, 2.9≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦5.2; 0.26≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.85, 1.17≦W(ZrO2) / W(P2O5)≦2.61, 2.5≦[W(SiO2)-6×W(Al2O3)-2×W(Li2O)] / W(Na2O)≦5.8.
[0018] In one embodiment, in weight percent: It contains 72.8-73.9% SiO2, 7.4-8% Al2O3, 2.1-2.6% P2O5, 10.7-11.7% Li2O, 0.9-1.4% Na2O and 3.9-4.4% ZrO2.
[0019] In one embodiment, 4.5≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦5.2; 0.42≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.66, 1.5≦W(ZrO2) / W(P2O5)≦2.1, 3.57≦[W(SiO2)-6×W(Al2O3)-2×W(Li2O)] / W(Na2O)≦5.
[0020] The present application relates to a composition comprising, in mass %, A glass composition is provided comprising 71.5-74% SiO2, 6.2-8.5% Al2O3, 1.7-2.6% P2O5, 0.1-1.7% B2O3, 10-12% Li2O, 0.1-2% Na2O, 0.1-1.5% CaO, and 3-5% ZrO2.
[0021] In one embodiment, in weight percent based on the oxide, It contains 72-73.5% SiO2, 6.8-8.2% Al2O3, 2-2.4% P2O5, 0.4-1.1% B2O3, 10.8-11.7% Li2O, 0.4-1.7% Na2O, 0.3-1% CaO and 3.3-4.4% ZrO2.
[0022] In one embodiment, 2≦[W(ZrO2)−W(CaO)] / [W(P2O5)−W(B2O3)]≦3.22.
[0023] In one embodiment, 2.06≦[W(ZrO2)-W(CaO)] / [W(P2O5)-W(B2O3)]≦2.31.
[0024] In one embodiment, 2.3≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦10.3; 0.27≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.87.
[0025] In one embodiment, 2.7≦W(SiO2)−6×W(Al2O3)−2×W(Li2O)≦7.8; 0.46≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.77.
[0026] The present application further provides a glass-ceramic comprising the glass composition as described above.
[0027] In one embodiment, the thickness of the crystallized glass is 0.3 to 1.5 mm.
[0028] The present application further provides a crystallized glass comprising the above glass composition, the crystallized glass having a crystalline phase Li2Si2O5 and a crystalline phase LiAlSi4O 10 Contains:
[0029] In one embodiment, 0.91≦W(LiSiO) / W(LiAlSiO 10 )≦1.06.
[0030] In one embodiment, 0.97≦W(LiSiO) / W(LiAlSiO 10 )≦1.03.
[0031] In one embodiment, 10.44≦M≦12.54; Here, M = 1.3 × [W(Li2Si2O5) / W(LiAlSi4O 10 )]×{0.86×[W(SiO2)-6×W(Al2O3)-2×W(Li2O)]+1.83×[(W(Li2O)-W(Al2O3)) / (W(P2O5)+W(Zr O2))]+1.67×[W(ZrO2) / W(P2O5)]+0.25×[(W(SiO2)-6×W(Al2O3)-2×W(Li2O)) / W(Na2O)]}.
[0032] In one embodiment, 11.85≦M≦12.54.
[0033] The present application provides a crystallized glass comprising the glass composition as described above.
[0034] In one embodiment, the crystalline glass is mainly composed of lithium disilicate and petalite, the total content of the crystalline glass is 60%-90%, the content of lithium disilicate is >30%, and the content of petalite is >30%. The present application further provides a method for producing crystallized glass, the method comprising: A step S10 of weighing the glass composition as described above; Step S20 of mixing and melting the glass composition, then fining, homogenizing, forming, annealing, and finally cutting to obtain a base glass; and step S30 of heat-treating the base glass to obtain crystallized glass.
[0035] In one embodiment, step S30 includes: The base glass is heated from room temperature to 510 to 540° C. in 20 to 60 minutes, and a first nucleation treatment is performed for 3 to 8 hours. The temperature is raised to 580-610°C in 5-30 min, and the second nucleation treatment is carried out for 3-8 h. The temperature is raised to 650-680°C in 5-30 minutes, and crystallization treatment is carried out for 3-8 hours. and cooling to room temperature to obtain a crystallized glass.
[0036] In one embodiment, the step of heat treating the base glass to obtain a crystallized glass comprises: The base glass is heated from room temperature to 530 to 570 ° C. in 20 to 60 minutes, and a nucleation treatment is performed for 3 hours or more. The temperature is raised to 680-720°C in 5-30 minutes, and the crystallization treatment is carried out for 3 hours or more. and cooling to room temperature to obtain the crystallized glass.
[0037] In one embodiment, after step S30, The step S40 includes pretreating the crystallized glass, then placing the glass in an ion exchange bath to perform a salt bath, thereby obtaining chemically strengthened crystallized glass; Here, the ion exchange bath contains, in mass %, 20 to 40% NaNO3 and 60 to 80% KNO3, and / or The salt bath strengthening temperature is 420 to 500 ° C., and / or The salt bath strengthening time is 3 to 8 hours.
[0038] In one embodiment, in step S20, the forming method includes float forming, overflow forming, calendar forming, or slot downdraw forming.
[0039] The present application further provides an electronic display terminal comprising the crystallized glass as described above. Effect of the Invention
[0040] In the technical solution of the present application, the components SiO2, Al2O3, P2O5, Li2O, Na2O and ZrO2 in the glass composition are combined with a specific gravity, and combined with a crystallization process and a strengthening process of the crystallized glass, so that the b value and haze can be significantly reduced and a crystallized glass with excellent strengthening performance can be obtained. [Brief description of the drawings]
[0041] In order to more clearly explain the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings that need to be used in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present application, and those skilled in the art can obtain other related drawings based on these drawings without any creative work.
[0042] [Figure 1] 1 is a schematic flow chart of one embodiment of a method for producing crystallized glass provided in the present application. [Diagram 2] 1 is a schematic flow chart of another embodiment of a method for producing crystallized glass provided herein. [Diagram 3] FIG. 2 is a linear relationship diagram between M and the fracture toughness KIC of glass-ceramics in the present application.
[0043] The realization of the object, features and advantages of the present invention will be further described with reference to the drawings in conjunction with the embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described below clearly and completely. Obviously, the described embodiments are only some embodiments of the present application, but not all embodiments.
[0045] In addition, if no specific conditions are specified in the examples, the procedures are performed according to normal conditions or manufacturer's recommended conditions. Reagents and instruments used without a manufacturer's name are all normal and commercially available. In addition, the meaning of "and / or" throughout this specification includes three parallel solutions, and for example, "A and / or B" includes technical solution A, or technical solution B, or a technical solution that satisfies A and B simultaneously. In addition, the technical solutions in each embodiment can be combined with each other, but this must be based on what can be realized by a person skilled in the art. If the combination of technical solutions is mutually contradictory or cannot be realized, such a combination of technical solutions should be considered to exist and is not included in the scope of protection claimed in this application. All other embodiments obtained based on the embodiments of this application without the creative labor of a person skilled in the art are within the scope of protection of this application.
[0046] With the development of display technology, glass is commonly used to protect display devices. The cover glass for protecting electronic products on the market generally belongs to high alumina silicate glass. High alumina is advantageous for improving the stress strength and stress layer depth after ion exchange, but the drop resistance of glass is poor. Some studies have shown that 70% of electronic product breakages are caused by careless drops.
[0047] The glass recipe is introduced with a nucleating agent or the composition ratio of oxides in the recipe is adjusted to form one or more crystal phases in the subsequent heat treatment process, which is called crystallized glass. Since it has not only the high transparency of glass but also the high strength of ceramics, it can improve the average hardness, fracture toughness, and other performance of glass. The microcrystalline phase in crystallized glass can block the propagation path of microcracks, which is advantageous for the overall improvement of the scratch resistance, impact resistance, drop resistance, and other performance of glass.
[0048] The performance of glass-ceramics is determined by the ratio of the crystal phase to the glass phase, the size of the crystal grains, etc. During the manufacturing process of glass-ceramics, factors such as the aggregation of glass composition, the interface form of the crystal phase, and the external form of the crystal grains cause currently manufactured transparent glass-ceramics to have a large b value, high haze, and macroscopically, transmitted light appears yellowish, which affects the transmittance and usage performance of the glass-ceramics.
[0049] In view of this, the present application provides a glass composition, and the glass-ceramics produced from the glass composition can effectively solve the problems of current transparent glass-ceramics having a large b value and high haze.
[0050] In an embodiment of the present application, a glass composition is provided that contains, in mass%, 71.5 to 74.5% SiO2, 6.2 to 8.7% Al2O3, 1.7 to 3% P2O5, 10 to 12.5% Li2O, 0.1 to 2% Na2O, and 3 to 5% ZrO2.
[0051] In another embodiment, the glass composition further comprises, in mass%, 0.1-1.7% B2O3 and / or 0.1-1.5% CaO.
[0052] In the embodiment of the present application, the composition is, in mass%, 71.5 to 74.5% SiO2, 7.3 to 8.7% Al2O3, 1.7 to 3% P2O5, 0.1 to 1% B2O3, 10.2 to 12% Li2O, A glass composition is provided that contains 0.4-1.5% Na2O and 3.1-5% ZrO2.
[0053] In an embodiment of the present application, there is provided a glass composition containing, in mass %, based on oxides, 71.5 to 74% SiO2, 6.2 to 8.5% Al2O3, 1.7 to 2.6% P2O5, 0.1 to 1.7% B2O3, 10 to 12% Li2O, 0.1 to 2% Na2O, 0.1 to 1.5% CaO, and 3 to 5% ZrO2.
[0054] The present application provides a glass composition, and the glass-ceramics produced from the glass composition can effectively solve the problems of a large b value and high haze, as well as the problems of a decrease in the crystal content and destruction of the interlocking structure of the twin phase that occur during chemical strengthening.
[0055] The glass composition contains, in mass%, 72 to 74.3% SiO2, 7 to 8.5% Al2O3, 1.8 to 3% P2O5, 10.2 to 12.5% Li2O, 0.5 to 2% Na2O, and 3.5 to 4.7% ZrO2.
[0056] First, the petalite molecular formula of the preferred crystallized glass phase of the present invention is LiAlSiO 10 and the molecular formula of lithium disilicate is Li2Si2O5. When calculating the mass% of each component, the sum of the masses of SiO2, Al2O3, P2O5, B2O3, Li2O, Na2O, and ZrO2 in the glass composition is used as the basis, or the sum of the masses of SiO2, Al2O3, P2O5, Li2O, Na2O, and ZrO2 in the glass composition is used as the basis.
[0057] The glass composition of the present invention is introduced with SiO2, which constitutes a component of the glass skeleton. SiO2, as the main component of the glass network structure, can impart excellent chemical stability, mechanical properties, and molding performance to the base glass and the crystallized glass. In the glass microcrystallization process, Li2Si2O5 and LiAlSi4O 10 To form a crystalline phase, SiO2 is provided, and if SiO2 is too high, it will promote the generation of quartz and quartz solid solution in the glass microcrystallization process. Therefore, considering the overall situation, the SiO2 content is selected to be 71.5wt%-74.5wt%, or the SiO2 content is selected to be 72wt%-74.3wt%, or the SiO2 content is selected to be 71.5wt%-74wt%.
[0058] The glass composition of the present application introduces Al2O3, which belongs to the network intermediate oxide. Non-bridging oxygen forms aluminum oxygen tetrahedrons with Al, whose volume is larger than that of silicon oxygen tetrahedrons, which creates larger gaps in the glass structure and is favorable for ion exchange, thereby improving the effect of chemical strengthening and improving the mechanical properties of glass. However, Al2O3 belongs to oxides with a very high melting point, which can rapidly increase the high-temperature viscosity of glass, which makes it difficult to clarify and homogenize glass, and greatly increases the concentration of bubble defects in glass. If the content of Al2O3 is too high, it can significantly increase the microcrystallization temperature of glass and suppress the crystallization ability of the base glass, making it difficult to form lithium disilicate, and the glass LiAlSi4O in the crystallization process will be difficult. 10 and further form LiAlSi2O6 crystal phase in the base glass, which reduces the transmittance of the glass. Therefore, taking into consideration all factors, the Al2O3 content is selected to be 7.3wt% to 8.7wt%, or the Al2O3 content is selected to be 6.2wt% to 8.5wt%, or the Al2O3 content is selected to be 7wt% to 8.5wt%.
[0059] The glass composition of the present application is introduced with P2O5, which is more likely to promote the crystallization of lithium disilicate crystals. 5+ The ions have a very large electric field strength and a strong ability to take away oxygen, which tends to strengthen the phosphorus-oxygen network structure. 5+ The ion is Si 4+ Since the electric field strength is greater than that of ions, P 5+ Li2O and P2O5 react to form Li3PO4 crystalline phase, which induces the reaction of Li2O and SiO2 in the glass to form Li2SiO3, and finally forms Li2Si2O5 crystalline phase. Furthermore, P2O5 is connected to the network by [PO4] tetrahedrons, so that the glass network structure is sparse and the network voids are large. Na in the glass is connected to the network by [PO4] tetrahedrons, so that the glass network structure is sparse and the network voids are large. + Ions and K in molten salts+ It is favorable for the interdiffusion with ions, and plays a role in promoting ion strengthening during the glass strengthening process, and plays an important role in obtaining a high compressive stress layer. However, if the P2O5 content is too high, it will promote the precipitation of lithium metasilicate during the crystallization process, resulting in an excessively small glass phase, which will not be able to form a sufficient Li2Si2O5 crystal phase and promote the precipitation of quartz phase, making it difficult to obtain highly transparent crystallized glass. Therefore, considering the overall situation, the P2O5 content should be selected to be 1.7wt%-3wt%, or the P2O5 content should be selected to be 1.8wt%-3wt%, or the P2O5 content should be selected to be 1.7wt%-2.6wt%.
[0060] The glass composition of the present application is introduced with B2O3, which can improve the melting property of glass and lower the melting point, and also helps to improve the scratch resistance of the glass surface. From the research of the present application, it has been found that B2O3 exists in the crystallized glass structure in the form of dense [BO4], effectively suppressing the problem of the increase in haze of the crystallized glass caused by the growth of petalite during the nucleation of lithium disilicate (>580°C), while restricting the movement of alkali metal ions in the crystallized glass, and stabilizing the crystal structure of the crystallized glass. Therefore, considering the overall situation, the content of B2O3 is selected to be 0.1wt% to 1.7wt%, or the content of B2O3 is selected to be 0.1wt% to 1wt%.
[0061] The glass composition of the present invention contains Li2O, which belongs to the outer network oxide, to reduce the viscosity of the glass and promote the melting and fining of the glass. + Li is the main exchange ion in the chemical strengthening process. + The ion has a small radius and is Li + The faster ion exchange rate of the Li-containing glass results in a thicker strengthening layer in the glass in a shorter time. + Ions and Na in the melt + ions are exchanged, and the rate is + and K. +The exchange rate with Li ions is faster than that of Li ions. The high Li2O concentration promotes the formation of Li3PO4 in the base microcrystallization process, which is helpful in the formation of lithium disilicate crystal phase and petalite crystal phase in the crystallization process, and the Na ions are used in the chemical strengthening process to realize the microcrystallized glass and obtain a deep ion strengthening layer depth. + and Li, which acts as a mutual reinforcement and reduces cracks on the surface of the crystallized glass. + must be present in sufficient amounts in the glass to provide the mechanical strength of the crystallized glass. However, if the Li2O content is too high, the viscosity of the glass will be too low, making it difficult to obtain a chemically stable glass composition, and the compressive stress value in the ion strengthening process will be too low, and the raw material cost will increase. Therefore, taking everything into consideration, the Li2O content should be selected to be 10.2wt%-12wt%, or the Li2O content should be selected to be 10.2wt%-12.5wt%, or the Li2O content should be selected to be 10wt%-12wt%.
[0062] The incorporation of Na2O into the glass composition of the present application significantly reduces the viscosity of the base glass, promotes melting and fining of the base glass, and lowers the crystallization temperature of the glass. + By promoting the strengthening of glass-ceramics by ions, high compressive stress is generated on the glass surface, improving the strength of the glass and adding Na to the glass. + Therefore, taking into consideration all factors, the Na2O content is selected to be 0.1wt% to 2wt%, or the Na2O content is selected to be 0.4wt% to 1.5wt%, or the Na2O content is selected to be 0.5wt% to 2wt%.
[0063] ZrO2 is introduced into the glass composition of the present application. On the one hand, the potential energy of zirconium ions is large, which can strengthen the glass network structure, and ZrO2 has a tendency to promote the crystallization of petalite crystals; on the other hand, ZrO2 is useful for reducing the size of crystal grains during the crystallization process, thereby improving the transmittance of glass and rapidly improving the chemical stability of glass. Secondly, it can improve the fracture toughness and bending strength of glass, and generate stress induction due to the crystal phase transition of zirconia itself, thereby improving the fracture toughness after crystallization. If the ZrO2 content is too high, there will be unmelted ZrO2 in the glass, which will prevent the glass from crystallizing uniformly. Therefore, taking into consideration the overall ZrO2 content is selected to be 3wt%-5wt%, or the ZrO2 content is selected to be 3.1wt%-5wt%, or the ZrO2 content is selected to be 3.5wt%-4.7wt%.
[0064] In the technical solution of the present application, the components SiO2, Al2O3, P2O5, B2O3, Li2O, Na2O and ZrO2 in the glass composition are combined with a specific specific gravity, and combined with a crystallization process and a strengthening process of the crystallized glass, so that the b value and haze can be significantly reduced and a crystallized glass with excellent strengthening performance can be obtained.
[0065] In addition, CaO can be introduced into the glass composition of the present application to improve the chemical stability and mechanical strength of the glass. CaO can more easily combine with acidic Al2O3 in the glass structure, affecting the coordination state of boron, and since CaO is more alkaline than Na2O, it can compensate for the negative charge of the [AlO4] tetrahedron, stabilizing the crystal phase structure in the crystallized glass. However, a high CaO content causes a decrease in devitrification resistance. Therefore, taking into consideration all factors, the CaO content is selected to be 0.1wt% to 1.5wt%.
[0066] In the technical solution provided in this application, the components SiO2, Al2O3, P2O5, B2O3, Li2O, Na2O, CaO and ZrO2 in the glass composition are combined with a specific specific gravity, and combined with the crystallization process and strengthening process of crystallized glass, which significantly improves the situation of the decrease in crystalline content and the destruction of the interlocking structure of the twin phase that occurs during the chemical strengthening process, and can obtain crystallized glass with excellent strengthening performance.
[0067] In one embodiment, the components in the glass composition include SiO2, Al2O3, P2O5, Li2O, Na2O, and ZrO2, and the relationship between each component of the glass composition satisfies 2.9≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦5.2. A=W(SiO2)-6×W(Al2O3)-2×W(Li2O), where W represents the mass% of the component relative to the total mass of all oxide components, and the A value is the molecular value of mass% calculated by the formula. When the A value is low, all of SiO2 enters the crystalline phase, whereas Al2O3 or Li2O is excessive, and when the A value is too high, all of Al2O3 or Li2O enters the crystalline phase, and the remaining SiO2 exists as a network skeleton structure in the glass phase, and the total crystalline phase content of the crystallized glass is low. In this way, by controlling the A value within the above range, the excess of Al2O3 or Li2O is avoided, and the total crystal phase content of the crystallized glass is effectively improved. Preferably, 4.5≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦5.2.
[0068] The relationship between the components of the glass composition satisfies 0.26≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.85. It is expressed as B=[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)], where W represents the mass% of the component relative to the total mass of all oxide components. If the B value is too low, undesirable crystal phases such as β-quartz are likely to occur, and the proportion of petalite crystal phase is high, so that crystal grains tend to grow, resulting in the proportion of microcrystals becoming translucent or devitrified. If the B value is too high, the proportion of the glass phase in the crystallized glass becomes large, and the superiority of the performance of the crystallized glass cannot be fully exhibited. In this way, by controlling the B value within the above range, the superiority of the performance of the crystallized glass is fully exhibited, and the proportion of microcrystals in the crystallized glass is prevented from becoming translucent or devitrified. Preferably, 0.42≦[W(Li2O)−W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.66.
[0069] The relationship between the components of the glass composition satisfies 1.17≦W(ZrO2) / W(P2O5)≦2.61. It is expressed as C1=W(ZrO2) / W(P2O5), where W represents the mass% of the component relative to the total mass of all oxide components. By controlling the C1 value within the above range, the activation energy of the liquid-liquid surface is reduced to cause phase separation, and nucleation and crystallization can be performed at a low temperature. In addition, the development of the phase interface due to the crystallization and unstable decomposition of the liquid phase is realized, which reduces the activation energy or energy barrier of nucleation, and reduces the nucleation temperature and crystallization temperature. The two types of crystalline phases compete for the silicon source and the lithium source, i.e., they destroy the crystalline phase structure already formed by the other crystalline phase and use it to form their own crystalline phase, and the amount of the crystalline phase of petalite and lithium disilicate formed is (W(Li2Si2O5) / W(LiAlSi4O 10)=0.91-1.06, details to be described later), the crystal size is uniform and <100 nm, and meets the basic requirement of optical visibility. If the C1 value is too high or too low, the single crystal phase becomes more abundant and is more likely to grow, the visible light transmittance of the crystallites decreases, and the haze increases. Preferably, 1.5≦W(ZrO2) / W(P2O5)≦2.1.
[0070] The relationship between each component of the glass composition satisfies 2.5≦[W(SiO2)-6×W(Al2O3)-2×W(Li2O)] / W(Na2O)≦5.8. It is expressed as D=[W(SiO2)-6×W(Al2O3)-2×W(Li2O)] / W(Na2O), where W represents the mass% of the component relative to the total mass of all oxide components. By controlling the D value within the above range, it is useful for stabilizing the glass crystal structure, particularly suppressing the movement of lithium ions during the strengthening process. The interlocking structure formed by the crystallized glass petalite and lithium disilicate is further maintained, improving the performance of the crystallized glass. If the D value is too high, the chemical strengthening ions of the crystallized glass are difficult to exchange, and if the D value is too low, the interlocking structure formed by the crystallized glass petalite and lithium disilicate cannot be maintained, and the microcrystalline structure is destroyed during the chemical strengthening process. Preferably, 3.57≦[W(SiO2)−6×W(Al2O3)−2×W(Li2O)] / W(Na2O)≦5.
[0071] In one embodiment, it is preferable that the components of the glass composition satisfy the conditions of SiO2 72.8-73.9%, Al2O3 7.4-8%, P2O5 2.1-2.6%, Li2O 10.7-11.7%, Na2O 0.9-1.4%, and ZrO2 3.9-4.4%, which further optimizes the performance of the crystallized glass obtained from the glass composition.
[0072] In one embodiment, the components in the glass composition include SiO2, Al2O3, P2O5, B2O3, Li2O, Na2O, and ZrO2, and the relationship between each component of the crystallized glass satisfies -1.1≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦6.7. It is written as A=W(SiO2)-6×W(Al2O3)-2×W(Li2O), where W represents the mass% of the component relative to the total mass of all components, and the A value is the molecular value of the mass% calculated by the formula. When the A value is low, all of SiO2 enters the crystalline phase, whereas Al2O3 or Li2O is excessive, and the formation rate of the petalite crystalline phase is high, and the crystal grains tend to grow, resulting in a rate of microcrystals that are translucent or devitrified. If the A value is too high, Al2O3 or Li2O will enter the crystalline phase entirely, and the remaining SiO2 will exist as a network structure in the glass phase, so that the total crystalline phase content of the crystallized glass is low. Thus, by controlling the A value within the above range, the proportion of microcrystals in the crystallized glass can be prevented from becoming translucent or devitrified, and the total crystalline phase content of the crystallized glass can be effectively improved.
[0073] The relationship between the components of the crystallized glass satisfies 0.19≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.98. It is expressed as B=[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)], where W represents the mass% of the component relative to the total mass of all components. If the B value is too low, the proportion of the glass phase in the crystallized glass becomes large, and the superiority of the performance of the crystallized glass cannot be fully exhibited. If the B value is too high, undesirable crystal phases such as β-quartz are likely to occur, and the proportion of the petalite crystal phase is high, and the crystal grains are likely to grow, so that the proportion of microcrystals becomes translucent or devitrified. In this way, by controlling the B value within the above range, the superiority of the performance of the crystallized glass is fully exhibited, and the proportion of microcrystals in the crystallized glass becomes translucent or devitrified.
[0074] The relationship between each component of the crystallized glass satisfies 0.06≦[W(ZrO2)-3×W(B2O3)] / W(P2O5)≦1.57. It is expressed as C2=[W(ZrO2)-3×W(B2O3)] / W(P2O5), where W represents the mass% of the component relative to the total mass of all components. By controlling the C2 value within the above range, the active energy of the liquid-liquid surface is reduced to cause phase separation, and nucleation and crystallization can be achieved at a low temperature. The development of the phase interface due to crystallization and unstable decomposition of the liquid phase is realized, lowering the active energy or energy barrier of nucleation, and lowering the nucleation temperature and crystallization temperature. The two crystalline phases compete for silicon and lithium sources, that is, they destroy the crystalline phase structure already formed by the other crystalline phase to form their own crystalline phase, and the crystalline phase amounts of the formed petalite and lithium disilicate are close, and the crystallite size is uniform and <100nm, which meets the basic requirements for optical visibility. If the C2 value is too high or too low, there will be more single crystalline phases and they will grow easily, which will reduce the visible light transmittance of the microcrystals and increase the haze.
[0075] In one embodiment, it is preferable that the components of the glass composition satisfy the following conditions: 72-74% SiO2, 7.5-8.4% Al2O3, 2-2.8% P2O5, 0.3-0.8% B2O3, 10.5-11.8% Li2O, 0.5-1.3% Na2O, and 3.4-4.7% ZrO2. This further optimizes the performance of the crystallized glass obtained from the glass composition.
[0076] With regard to the blending ratio of each component of the glass composition, it is more preferable that the ratios between each component of the crystallized glass satisfy 0.6≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦5.4, 0.28≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.8, and 0.5≦[W(ZrO2)-3×W(B2O3)] / W(P2O5)≦1.36.
[0077] In one embodiment, the components of the glass composition satisfy the following conditions: 72.5-73.5% SiO2, 7.7-8% Al2O3, 2.1-2.5% P2O5, 0.5-0.7% B2O3, 11-11.5% Li2O, 0.7-1.1% Na2O, and 3.8-4.4% ZrO2. This provides better performance for the crystallized glass obtained from the glass composition.
[0078] With regard to the blending ratio of each component of the glass composition, it is more preferable that the components of the crystallized glass satisfy 2.5≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦4.3, 0.43≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.64, and 0.81≦[W(ZrO2)-3×W(B2O3)] / W(P2O5)≦1.16.
[0079] In one embodiment, it is preferable that each component of the glass composition satisfies the conditions of 72-73.5% SiO2, 6.8-8.2% Al2O3, 2-2.4% P2O5, 0.4-1.1% B2O3, 10.8-11.7% Li2O, 0.4-1.7% Na2O, 0.3-1% CaO, and 3.3-4.4% ZrO2, which further optimizes the performance of the crystallized glass obtained from the glass composition.
[0080] In one embodiment, the components in the glass composition include SiO2, Al2O3, P2O5, B2O3, Li2O, Na2O, CaO, and ZrO2, and the relationship between each component of the glass composition satisfies 2.3≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦10.3. It is expressed as A=W(SiO2)-6×W(Al2O3)-2×W(Li2O), where W represents the mass% of the component, and the A value is the molecular value of the mass% calculated by the formula. When the A value is low, all of the SiO2 enters the crystalline phase, whereas Al2O3 or Li2O is in excess, the formation rate of the petalite crystalline phase is high, and the crystal grains tend to grow, leading to a rate of microcrystals becoming translucent or devitrified. When the A value is too high, all of the Al2O3 or Li2O enters the crystalline phase, and the remaining SiO2 exists as a network skeleton structure in the glass phase, and the total crystalline phase content of the crystallized glass is low. In this way, by controlling the A value within the above range, the proportion of microcrystals in the crystallized glass is prevented from becoming translucent or devitrified, and the total crystal phase content of the crystallized glass is effectively improved. In one embodiment, it is preferable that 2.7≦W(SiO2)-6×W(Al2O3)-2×W(Li2O)≦7.8.
[0081] The relationship between the components of the glass composition satisfies 0.27≦[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.87. It is expressed as B=[W(Li2O)-W(Al2O3)] / [W(P2O5)+W(ZrO2)], where W represents the mass% of the component. If the B value is too low, the proportion of the glass phase in the crystallized glass becomes large, and the superiority of the performance of the crystallized glass cannot be fully exhibited. If the B value is too high, undesirable crystal phases such as β-quartz are likely to occur, and the proportion of the petalite crystal phase is high, and crystal grains are likely to grow, leading to the proportion of microcrystals becoming translucent or devitrified. In this way, by controlling the B value within the above range, the superiority of the performance of the crystallized glass is fully exhibited, and the proportion of microcrystals in the crystallized glass becoming translucent or devitrified is avoided. In one embodiment, it is preferred that 0.46≦[W(Li2O)−W(Al2O3)] / [W(P2O5)+W(ZrO2)]≦0.77.
[0082] The relationship between each component of the glass composition satisfies 2≦[W(ZrO2)-W(CaO)] / [W(P2O5)-W(B2O3)]≦3.22. C3=[W(ZrO2)-W(CaO)] / [W(P2O5)-W(B2O3)], where W represents the mass% of the component. By controlling the C3 value within the above range, on the one hand, the active energy of the liquid-liquid surface is reduced to cause phase separation, nucleation and crystallization can be achieved at a low temperature, the amount of crystalline phase of the formed petalite and lithium disilicate is close, the crystal size is uniform and is <100 nm, and the basic requirements for optical visibility are met. On the other hand, the glass crystal structure is stabilized, and especially in the chemical strengthening process, the migration of lithium ions is inhibited, and the crystal content of the crystallized glass after chemical strengthening is improved. In addition, if the C3 value is too high or too low, it will affect the microcrystal visible light transmittance, b value, and haze. In one embodiment, it is preferred that 2.06≦[W(ZrO2)-W(CaO)] / [W(P2O5)-W(B2O3)]≦2.31.
[0083] In the embodiment of the present application, there is further provided a crystallized glass comprising the above-mentioned glass composition. The crystallized glass comprises all the technical features of the above-mentioned glass composition, and therefore has all the technical effects of the above-mentioned glass composition, and thus will not be described here one by one.
[0084] In one embodiment, the thickness of the crystallized glass is 0.3 to 1.5 mm. The thinner the plate thickness of the crystallized glass is, the lighter the crystallized glass can be.
[0085] In one embodiment, the crystalline phase of the crystallized glass is mainly lithium disilicate and petalite, the total content of the crystalline phase of the crystallized glass is 60%-90%, the content of the lithium disilicate is >30%, and the content of the petalite is >30%.By ensuring that the lithium disilicate and petalite are within this range, the crystalline phase content of the crystallized glass is increased and the ratio of two crystalline phases is well balanced, so that the strengthening performance of the crystallized glass is better.
[0086] In one embodiment, the thickness of the crystallized glass is 0.3 to 1.5 mm. The thinner the plate thickness of the crystallized glass is, the lighter the crystallized glass can be.
[0087] In the embodiment of the present application, there is further provided a crystallized glass comprising the above-mentioned glass composition, and the crystallized glass has a crystalline phase Li2Si2O5 and a crystalline phase LiAlSi4O 10 The crystallized glass includes all the technical features of the above glass composition, and therefore has all the technical effects of the above glass composition, and thus will not be described here one by one.
[0088] The crystallized glass has a relationship of 0.91≦W(Li2Si2O5) / W(LiAlSi4O 10 )≦1.06. E=W(Li2Si2O5) / W(LiAlSi4O 10 ), where W represents the mass % of the crystal phase relative to the crystallized glass. By controlling the E value within the above range, it is ensured that the amounts of the formed petalite and lithium disilicate crystal phases are close to each other, further improving the performance of the crystallized glass. 0.97≦W(Li2Si2O5) / W(LiAlSi4O 10 )≦1.03 is even more preferable.
[0089] The crystallized glass must also satisfy 10.44≦M≦12.54, where M=1.3×[W(Li2Si2O5) / W(LiAlSi4O 10)]×{0.86×[W(SiO2)-6×W(Al2O3)-2×W(Li2O)]+1.83×[(W(Li2O)-W(Al2O3)) / (W(P2O5)+W(ZrO2))]+1.67×[W(ZrO2) / W(P2O5)]+0.25×[(W(SiO2)-6×W(Al2O3)-2×W(Li2O)) / W(Na2O)]}. That is, M=1.3×E×(0.86×A+1.83×B+1.67×C+0.25×D), and research has found that M has a linear relationship with the fracture toughness KIC of crystallized glass, and that controlling the M value within the above range based on this linear relationship is helpful in improving the fracture toughness of crystallized glass, as shown in Figure 3. It is even more preferable that 11.85≦M≦12.54.
[0090] In one embodiment, the thickness of the crystallized glass is 0.3 to 1.5 mm. The thinner the plate thickness of the crystallized glass is, the lighter the crystallized glass can be.
[0091] Furthermore, the present application further provides a method for producing the above-mentioned crystallized glass, which includes steps S10 to S30 as shown in FIG.
[0092] In S10, the above-mentioned glass composition is weighed.
[0093] In S20, the glass composition is mixed and melted, then refined, homogenized, formed, annealed, and finally cut to obtain a base glass.
[0094] Specifically, in step S20, the forming method includes float forming, overflow forming, calendar forming or slot downdraw forming. Other processes such as fining, homogenization, annealing and cutting are common processes in the field of glass technology, and detailed description is omitted here, but after obtaining the above processes, the thickness of the obtained base glass is 0.3-1.5 mm.
[0095] In S30, the base glass is heat-treated to obtain crystallized glass.
[0096] Specifically, step S30 includes heating the base glass from room temperature to 510-540°C in 20-60 minutes, performing a first nucleation treatment for 3-8 hours, heating it to 580-610°C in 5-30 minutes, performing a second nucleation treatment for 3-8 hours, heating it to 650-680°C in 5-30 minutes, performing a crystallization treatment for 3-8 hours, and cooling it to room temperature to obtain crystallized glass.
[0097] In one embodiment, as shown in FIG. 2, after step S30, The method includes a step S40 of pretreating the crystallized glass, placing the glass in an ion exchange bath for salt bathing, and obtaining chemically strengthened crystallized glass, in which the ion exchange bath contains, by mass %, 20-40% NaNO3 and 60-80% KNO3, the salt bath strengthening temperature is 420-500°C, and the salt bath strengthening time is 3-8 hours.
[0098] Due to the high content of crystals in the crystallized glass, there exists a structural difference between the glass phase and the crystal phase, forming structural cavities. When using molten salt containing >40wt%NaNO3, NaNO3 is released in a short time during ion exchange. + / Li + can reach deep ion depths, but Na + tends to aggregate in the cavities of the microcrystalline phase and the glass phase, making it difficult to form compressive stress. + / Li + If the exchange rate is too fast, the difference between the glass phase and the microcrystalline phase will become even larger over time, which is likely to cause an increase in the b value.
[0099] When the above strengthening regime is adopted, Na in the crystalline phase + / Li + The exchange rate of Na can be slowed down, and the Na in the cavities of the microcrystalline and glassy phases can be prevented. +It is favorable to reduce the aggregation of glass, effectively form compressive stress, reduce the glass phase and exchange rate, reduce the difference between the glass phase and the crystalline phase, and further reduce the b value of the glass.
[0100] In step S40, the pretreatment step specifically includes keeping the crystallized glass at 300 to 330° C. for 5 to 20 minutes. A detailed description of the general means in the technical field for pretreating the glass will be omitted here.
[0101] The present application further provides an electronic display terminal comprising the above-mentioned crystallized glass, the specific features of the crystallized glass can be referred to the above-mentioned embodiment, the electronic display terminal adopts all the technical solutions of all the above-mentioned embodiments, and at least has all the beneficial effects of the technical solutions of the above-mentioned embodiment, which will not be described one by one here. Wherein, the crystallized glass is used as a protective glass or protective member of the electronic display terminal, or the crystallized glass is used as a protective glass of a smart terminal, or the crystallized glass is used as a protective glass of a solar cell. EXAMPLES
[0102] The technical solution of the present application will be described in more detail below with reference to specific examples and drawings. It should be understood that the following examples are only for the purpose of interpreting the present application, and are not intended to limit the present application.
[0103] (Example) (1) A glass composition was weighed and contained, by mass%, 72% SiO, 37% AlO, 53% PO, 12.5% LiO, 2% NaO, and 3.5% ZrO.
[0104] (2) The glass composition was mixed and melted, then clarified, homogenized, formed, annealed, and finally cut to obtain a base glass.
[0105] (3) The base glass was heated from room temperature to 530°C in 20 minutes, subjected to nucleation treatment for 3 hours, heated to 680°C in 30 minutes, subjected to crystallization treatment for 3 hours, and cooled to room temperature to obtain crystallized glass.
[0106] (4) An ion exchange bath containing, by mass, 40% NaNO3 and 60% KNO3 was provided. After the crystallized glass was pretreated, it was placed in the ion exchange bath and subjected to a salt bath treatment to obtain chemically strengthened crystallized glass. The salt bath strengthening temperature was 420°C and the salt bath strengthening time was 3 hours.
[0107] The raw materials were weighed according to the glass composition component blend ratios of each example shown in Tables I1 and I2, and the other crystallized glasses and chemically strengthened crystallized glasses of Examples A2 to A14 were manufactured by referring to the manufacturing method of Example A1.
[0108] Raw materials were weighed according to the glass composition component blending ratios of Comparative Examples A1 to A5 shown in Table I3, and the crystallized glasses and chemically strengthened crystallized glasses of Comparative Examples A1 to A5 were produced by referring to the production method of Example A1.
[0109] The glass compositions of Examples A8 and A14 were subjected to steps (1) to (3) of the manufacturing method in Example A1 to manufacture crystallized glass. For specific process parameters during manufacturing, see Table I4.
[0110] The glass compositions of Examples A8 and A14 were subjected to steps (1) to (4) of the manufacturing method in Example A1 to produce chemically strengthened crystallized glass. The specific process parameters of manufacturing step (4) refer to Table I5, and the remaining steps (1) to (3) were the same as those of Example A1.
[0111] (Test Example) The test method and test equipment are as follows:
[0112] The main crystalline phase was tested by X-ray diffraction analyzer.
[0113] The crystal appearance morphology was observed by scanning electron microscope.
[0114] Color b-values were tested using a Datacolor650 ultra-high precision desktop spectrophotometer.
[0115] Visible light transmittance tests were performed using a spectrophotometer according to standard ISO13468-1:1996.
[0116] The haze of the glass was measured according to the ASTM D1003-92 test.
[0117] Glass fracture toughness KIC was measured according to ASTM E-1820 and is expressed in units of MPa m 1 / 2 It is.
[0118] The drop performance of the whole machine sandpaper is measured by the mobile phone control drop tester, and the specific test conditions are: 180 mesh sandpaper, a total weight of 195g, a base height of 60cm, increasing by 5cm, once for each height, until it breaks.
[0119] According to the test methods and test equipment of the test examples, the performance of the crystallized glass and chemically strengthened crystallized glass obtained in Examples B1 to B14, the crystallized glass and chemically strengthened crystallized glass obtained in Comparative Examples A1 to A5, the crystallized glass manufactured according to the process parameters in Table I4, and the chemically strengthened crystallized glass manufactured according to the process parameters in Table I5 were tested and entered into the corresponding tables.
[0120] It should be understood that the above test methods and test equipment are methods commonly used in the art to evaluate the relevant performance of glass, and are merely one of the means to characterize or evaluate the technical solutions and technical effects of the present application, and other test methods and test equipment may be adopted and will not affect the final results.
[0121] [Table 1.1]
[0122] [Table 1.2]
[0123] [Table 1.3]
[0124] [Table 1.4]
[0125] Here, the time in the nucleation process and the crystallization process represents the time required for heating, the temperature represents the target temperature to which the temperature is to be raised, and the time represents the treatment time.
[0126] [Table 1.5]
[0127] As can be seen from the test results of the performance of the crystallized glass of each embodiment shown in Tables I1, I2, I4 and I5, in the embodiments A1 to A14 using the technical solution of the present application, the crystallized glass obtained after the heat treatment has a crystalline phase of lithium disilicate Li2Si2O5>30%, a crystalline phase of petalite LiAlSi4O 10 The glass-ceramics had a 0.7 mm transmittance of >91%, a haze of <0.17, and a b-value of <0.4. The glass-ceramics had an average crystallite size of <100 nm. The glass-ceramics had a fracture toughness KIC of >1.1 MPa m 1 / 2 , the drop resistance was >200cm.
[0128] As can be seen from Table I3, in Comparative Example A1, SiO2=71.5%, A=0.5, and D=0.42. This does not meet the requirements of the glass composition of the present application, and the heat-treated crystallized glass is Li2Si2O5 / LiAlSi4O 10= 0.81, crystal size > 100 nm, transmittance was low, b value was too large, haze was large, and mechanical properties after chemical strengthening were poor.
[0129] In Comparative Example A2, A=8 and D=6.67. This does not meet the requirements of the glass composition of the present application, and the content of the microcrystalline phase in the heat-treated crystallized glass is low, and the Li2Si2O5 / LiAlSi4O 10 =0.6, and the mechanical properties after chemical strengthening were poor.
[0130] In Comparative Example A3, Li2O=10% and B=0.2. This does not meet the requirements of the glass composition of the present application, and the content of the microcrystalline phase in the heat-treated crystallized glass is low, and the Li2Si2O5 / LiAlSi4O 10 = 0.74, crystal size > 100 nm, transmittance was low, b value was too large, haze was large, and mechanical properties after chemical strengthening were poor.
[0131] In Comparative Example A4, P2O5=1.7%, A=2.1, C1=2.82, and D=2.33. This does not meet the requirements of the glass composition of the present application, and the content of the microcrystalline phase in the heat-treated glass-ceramics is low, and the Li2Si2O5 / LiAlSi4O 10 = 0.55, crystal size > 100 nm, transmittance was low, b value was too large, haze was large, and mechanical properties after chemical strengthening were poor.
[0132] In Comparative Example A5, P2O5=3.8%, A=2.7, C1=0.97, and D=2.45. This does not meet the requirements of the glass composition of the present application, and the content of the microcrystalline phase in the heat-treated glass-ceramics is low, and the Li2Si2O5 / LiAlSi4O 10 = 1.7, crystal size > 100 nm, transmittance was low, b value was too large, haze was large, and mechanical properties after chemical strengthening were poor.
[0133] The fracture toughness KIC value (1.012 to 1.78 MPa m) of the chemically strengthened glass-ceramics in the examples of this application 1 / 2 ) is the fracture toughness KIC value (0.43 to 0.72 MPa m) of the chemically strengthened glass ceramic in the comparative example.1 / 2 ), which explains that the decrease in crystal content and the destruction of the interlocking structure of the twin phase that occurs in the glass-ceramics of the examples of the present application during the chemical strengthening process are significantly improved, and it is clear that the b value and haze of the glass-ceramics of the examples of the present application are lower than the high b value and high haze of the glass-ceramics of the comparative examples, which explains that the glass-ceramics of the examples of the present application have achieved a decrease in b value and haze. Finally, the obtained chemically strengthened glass-ceramics has excellent strengthening performance.
[0134] (Example) (1) A glass composition was weighed and contained, by mass, 71.5% SiO2, 8.7% Al2O3, 53% P2O, 0.1% B2O3, 10.2% Li2O, 1.5% Na2O, and 5% ZrO2, with A=-1.1, B=0.19, and C2=1.57.
[0135] (2) The glass composition was mixed and melted, then clarified, homogenized, formed, annealed, and finally cut to obtain a base glass.
[0136] (3) The base glass was heated from room temperature to 510°C in 20 minutes, subjected to a first nucleation treatment for 3 hours, heated to 580°C in 5 minutes, subjected to a second nucleation treatment for 3 hours, heated to 650°C in 30 minutes, subjected to a crystallization treatment for 3 hours, and cooled to room temperature to obtain crystallized glass.
[0137] (4) After the crystallized glass was pretreated, it was placed in an ion exchange bath and salt-bathed to obtain chemically strengthened crystallized glass. The ion exchange bath contained, by mass%, 20% NaNO3 and 80% KNO3, the salt bath strengthening temperature was 420°C, and the salt bath strengthening time was 3 hours.
[0138] The raw materials were weighed according to the glass composition component blending ratios of each example shown in Tables II1 and II2, and the crystallized glasses and chemically strengthened crystallized glasses of other examples B2 to B15 were manufactured by referring to the manufacturing method of example B1.
[0139] Raw materials were weighed according to the blending ratios of glass composition components of Comparative Examples B1 to B7 shown in Table II3, and the crystallized glasses and chemically strengthened crystallized glasses of Comparative Examples B1 to B7 were produced respectively with reference to the production method of Example B1.
[0140] The glass compositions of Examples B1 and B9 were subjected to steps (1) to (3) of the manufacturing method of Example B1 to manufacture crystallized glass. For specific process parameters during manufacturing, see Table II4.
[0141] (Test Example) The test method and test equipment are as follows:
[0142] The main crystalline phase was tested by X-ray diffraction analyzer.
[0143] The crystal appearance morphology was observed by scanning electron microscope.
[0144] Color b-values were tested using a Datacolor650 ultra-high precision desktop spectrophotometer.
[0145] Visible light transmittance tests were performed using a spectrophotometer according to standard ISO13468-1:1996.
[0146] The haze of the glass was measured according to the ASTM D1003-92 test.
[0147] The drop performance of the whole machine sandpaper is measured by a mobile phone control drop tester, and the specific test conditions are: 180 mesh sandpaper, a total weight of 195g, a base height of 60cm, and an increase of 5cm, one time per height, until it breaks.
[0148] According to the test methods and test equipment of the test examples, the performances of the crystallized glass and chemically strengthened crystallized glass obtained in Examples B1 to B15, the crystallized glass and chemically strengthened crystallized glass obtained in Comparative Examples B1 to B7, and the crystallized glass manufactured according to the process parameters in Table II4 were tested and entered into the corresponding tables.
[0149] It should be understood that the above test methods and test equipment are methods commonly used in the art to evaluate the relevant performance of glass, and are merely one of the means to characterize or evaluate the technical solutions and technical effects of the present application, and other test methods and test equipment may be adopted and will not affect the final results.
[0150] [Table 2.1]
[0151] [Table 2.2]
[0152] [Table 2.3]
[0153] [Table 2.4]
[0154] Here, the time in the first nucleation treatment, the second nucleation treatment and the crystallization treatment indicates the time required for heating, the temperature indicates the target heating temperature, and the time indicates the treatment time.
[0155] As can be seen from the test results of the glass performance of each example shown in Tables II1, II2 and II4, in Examples B1 to B15 using the technical solution of the present application, lithium disilicate Li2Si2O5 accounts for 30% to 45% in the crystallized glass, and petalite LiAlSi4O 10 The crystallites account for 30%-45% of the glass, and the total crystalline phase accounts for 60%-90% of the glass. The crystallites are uniform in size, with an average crystallite size of <100nm. At a wavelength of 560nm, the 0.7mm glass has a transmittance of >91%, a haze of <0.17, a b value of <0.5, and a drop resistance of >200cm.
[0156] As can be seen from Table II3, in Comparative Example 1, B2O3=0%, C2=1.58. The heat-treated crystallized glass did not meet the requirements of the glass composition of the present application, and had a low microcrystalline phase content, a crystallite size of >100 nm, a low transmittance, a too large b value, and a large haze.
[0157] In Comparative Example B2, B2O3=1.1%, but C2=-0.22. The heat-treated crystallized glass did not meet the requirements of the glass composition of the present application, and had a low microcrystalline phase content, a crystal size of >100 nm, low transmittance, too large b value, high haze, and poor drop resistance.
[0158] In Comparative Example B3, Al2O3=9.5%, A=-4.8, B=0.08. The heat-treated crystallized glass did not meet the requirements of the glass composition of the present application, and had a low microcrystalline phase content, a crystal size of >100 nm, low transmittance, too large b value, high haze, and poor drop resistance.
[0159] In Comparative Example B4, SiO2=74.7% and A=12.1. This did not meet the requirements of the glass composition of the present application, the content of the microcrystalline phase in the heat-treated crystallized glass was low, and the drop resistance was poor.
[0160] In Comparative Example B5, Li2O=13%, B=1.08. The heat-treated crystallized glass did not meet the requirements of the glass composition of the present application, and had a low microcrystalline phase content, a crystallite size of >100 nm, low transmittance, too large b value, and high haze.
[0161] In Comparative Example B6, Al2O3=9%, B=-0.06. This did not meet the requirements of the glass composition of the present application, the content of the microcrystalline phase in the heat-treated crystallized glass was low, and the drop resistance was poor.
[0162] In Comparative Example B7, the glass components were within the requirements of the present application, but C2=1.91, which did not meet the requirements of the glass composition of the present application. The heat-treated crystallized glass had a low microcrystalline phase content, a crystallite size of >100 nm, a low transmittance, a too large b value, and a large haze.
[0163] The b value of the crystallized glass in the examples of the present application is significantly smaller than the b value and haze of the crystallized glass in the comparative examples, and the haze is significantly reduced. This demonstrates that the examples of the present application can effectively solve the problem of currently produced transparent crystallized glass having a large b value and high haze, and that the obtained crystallized glass has excellent strengthening performance.
[0164] (Example) (1) A glass composition was weighed and contained, by mass, 71.5% SiO2, 6.2% Al2O3, 51.7% P2O, 0.1% B2O3, 12% Li2O, 2% Na2O, 1.5% CaO, and 5% ZrO, with A=10.3, B=0.87, and C3=2.19.
[0165] (2) The glass composition was mixed and melted, then clarified, homogenized, formed, annealed, and finally cut to obtain a base glass.
[0166] (3) The base glass was heated from room temperature to 510°C in 20 minutes, subjected to a first nucleation treatment for 3 hours, heated to 580°C in 5 minutes, subjected to a second nucleation treatment for 3 hours, heated to 650°C in 30 minutes, subjected to a crystallization treatment for 3 hours, and cooled to room temperature to obtain crystallized glass.
[0167] (4) After the crystallized glass was pretreated, it was placed in an ion exchange bath and subjected to a salt bath treatment to obtain chemically strengthened crystallized glass. The ion exchange bath contained, by mass%, 40% NaNO3 and 60% KNO3, the salt bath strengthening temperature was 500°C, and the salt bath strengthening time was 8 hours.
[0168] The raw materials were weighed according to the glass composition component blending ratios of each example shown in Tables III1 and III2, and the crystallized glasses and chemically strengthened crystallized glasses of other examples C2 to C16 were manufactured by referring to the manufacturing method of example C1.
[0169] Raw materials were weighed according to the blending ratios of glass composition components of Comparative Examples C1 to C6 shown in Table III3, and the crystallized glasses and chemically strengthened crystallized glasses of Comparative Examples C1 to C6 were produced according to the production method of Example C1.
[0170] The glass compositions of Examples C1 and C8 were subjected to steps (1) to (3) of the manufacturing method of Example C1 to manufacture crystallized glass. For specific process parameters during manufacturing, see Table III4.
[0171] The glass compositions of Examples C1 and C8 were subjected to steps (1) to (4) of the manufacturing method in Example C1 to produce chemically strengthened crystallized glass. The specific process parameters of step (4) during the manufacturing process refer to Table III5, and the remaining steps (1) to (3) were the same as those of Example C1.
[0172] (Test Example) The test method and test equipment are as follows:
[0173] The main crystalline phase was tested by X-ray diffraction analyzer.
[0174] The crystal appearance morphology was observed by scanning electron microscope.
[0175] Color b-values were tested using a Datacolor650 ultra-high precision desktop spectrophotometer.
[0176] Visible light transmittance tests were performed using a spectrophotometer according to standard ISO13468-1:1996.
[0177] The haze of the glass was measured according to the ASTM D1003-92 test.
[0178] The drop performance of the whole machine sandpaper is measured by a mobile phone control drop tester, and the specific test conditions are: 180 mesh sandpaper, a total weight of 195g, a base height of 60cm, and an increase of 5cm, one time per height, until it breaks.
[0179] According to the test methods and test equipment of the test examples, the performances of the crystallized glass and chemically strengthened crystallized glass obtained in Examples C1 to C16, the crystallized glass and chemically strengthened crystallized glass obtained in Comparative Examples C1 to C6, the crystallized glass manufactured according to the process parameters in Table III4, and the chemically strengthened crystallized glass manufactured according to the process parameters in Table III5 were tested and entered into the corresponding tables.
[0180] It should be understood that the above test methods and test equipment are methods commonly used in the art to evaluate the relevant performance of glass, and are merely one of the means to characterize or evaluate the technical solutions and technical effects of the present application, and other test methods and test equipment may be adopted and will not affect the final results.
[0181] [Table 3.1]
[0182] [Table 3.2]
[0183] [Table 3.3]
[0184] [Table 3.4]
[0185] Here, the time in the first nucleation treatment, the second nucleation treatment and the crystallization treatment indicates the time required for heating, the temperature indicates the target heating temperature, and the time indicates the treatment time.
[0186] [Table 3.5]
[0187] As can be seen from the test results of the glass performance of each embodiment shown in Tables III1, III2, III4 and III5, in the embodiments C1 to C16 using the technical proposal of the present application, the chemically strengthened crystallized glass is composed of lithium disilicate Li2Si2O5>30%, petalite LiAlSi4O 10 >30%, the total content of the crystalline phase of the crystallized glass and the total content of the crystalline phase of the chemically strengthened crystallized glass were both 60%-90%, the average crystal size of the crystal grains in the crystallized glass was <100nm, the crystallized glass had a 0.7mm visible light transmittance of >91%, and a drop resistance of >200cm.
[0188] As can be seen from Table III3, in Comparative Example C1, Al2O3=9%, A=-4, and C3=1. The heat-treated crystallized glass did not meet the requirements of the glass composition of the present application, and had a low microcrystalline phase content, a crystallite size >100 nm, a low transmittance, a too large b value, and a large haze.
[0189] In Comparative Example C2, Al2O3=5.5%, A=18.5, and C3=1.2. This did not meet the requirements of the glass composition of the present application, and the content of the microcrystalline phase in the heat-treated crystallized glass was low, resulting in relatively poor drop resistance.
[0190] In Comparative Example C3, Li2O=12.5%, B=1.04, and C3=1.1. It did not meet the requirements of the glass composition of the present application, the heat-treated crystallized glass crystal size was >100 nm, the transmittance was low, the b value was too large, and the haze was large.
[0191] In Comparative Example C4, Li2O=9%, B=0.15, and C3=1.22. The glass composition did not meet the requirements of the present application, and the crystallized glass had a low crystalline phase content after being tempered, and the drop resistance performance was relatively poor.
[0192] In comparative example C5, CaO=1.6%, ZrO2=2.6%, C3=0.43, it does not meet the requirements of the glass composition of the present application, the heat-treated crystallized glass crystal size is >100nm, the transmittance is low, the b value is too large, the haze is large, the crystallized glass has a low crystalline phase content after being tempered, and the drop resistance is relatively poor.
[0193] In comparative example C6, B2O3=0, C3=1.64, it does not meet the requirements of the glass composition of the present application, the heat-treated crystallized glass crystal size is >100nm, the transmittance is low, the b value is too large, the haze is large, the crystallized glass has a low crystalline phase content after being tempered, and the drop resistance is relatively poor.
[0194] The reduction in the total content of the crystalline phase of the chemically strengthened glass-ceramics in the examples of the present application is smaller than the reduction in the total content of the crystalline phase of the chemically strengthened glass-ceramics in the comparative examples, which shows that the reduction in the crystal content and the destruction of the twin phase c that occur in the chemically strengthened glass-ceramics in the examples of the present application during the chemical strengthening process are significantly improved, and the obtained chemically strengthened glass-ceramics has excellent strengthening performance.
[0195] The above is only a preferred embodiment of the present application, and does not limit the scope of the patent of the present application. Those skilled in the art can make various modifications and variations of the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application should be included in the patent protection scope of the present application.
Claims
1. In mass percent, 71.5 to 74.5% SiO 2 , 6.2 to 8.7% Al 2 O 3 , 1.7-3% P 2 O 5 , 10~12.5%のLi 2 O、 0.1-2% Na 2 O, and 3-5% ZrO 2 A glass composition comprising:
2. 0.1-1.7% B 2 O 3 and / or 0.1 to 1.5% CaO.
3. -1.1≦W(SiO 2 ) -6 × W(Al 2 O 3 ) -2 × W (Li 2 3. The glass composition of claim 2, wherein O)≦6.
7.
4. 0.19≦[W(Li 2 O)-W(Al 2 O 3 )] / [W(P 2 O 5 ) + W(ZrO 2 3. The glass composition according to claim 2, wherein x = 0.
98.
5. 0.06≦[W(ZrO 2 ) - 3 × W(B 2 O 3 ) ] / W (P 2 O 5 3. The glass composition of claim 2, wherein σ is less than 1.
57.
6. In mass percent, 72-74% SiO 2 , 7.5 to 8.4% Al 2 O 3 , 2-2.8% P 2 O 5 , 0.3-0.8% B 2 O 3 , 10.5~11.8%のLi 2 O、 0.5-1.3% Na 2 O, and 3.4 to 4.7% ZrO 2 The glass composition of claim 2 , comprising:
7. 0.6≦W(SiO 2 ) -6 × W(Al 2 O 3 ) -2 × W (Li 2 O)≦5.4, <h2 style=";text-align:left;direction:ltr">1222≦[W(Li<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O)-W(Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ()] / [W(P<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 5 <h2 style=";text-align:left;direction:ltr"> ()+W(ZrO<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> )]≦0.8であり、 0.5≦[W(ZrO 2 ) - 3 × W(B 2 O 3 ) ] / W (P 2 O 5 7. The glass composition according to claim 6, wherein σ is less than 1.
36.
8. 2.9≦W(SiO 2 ) -6 × W(Al 2 O 3 ) -2 × W (Li 2 O)≦5.2; <h2 style=";text-align:left;direction:ltr">5225≦[W(Li<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O)-W(Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ()] / [W(P<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 5 <h2 style=";text-align:left;direction:ltr"> ()+W(ZrO<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> )]≦0.85であり、 1.17≦W(ZrO 2 ) / W (P 2 O 5 )≦2.61; 2.5≦[W(SiO 2 ) -6 × W(Al 2 O 3 ) -2 × W (Li 2 O)] / W(Na 2 3. The glass composition of claim 2, wherein O)≦5.
8.
9. 2≦[W(ZrO 2 )-W(CaO)] / [W(P 2 O 5 ) -W(B 2 O 3 3. The glass composition according to claim 2, characterized in that:
10. 2.06≦[W(ZrO 2 )-W(CaO)] / [W(P 2 O 5 ) -W(B 2 O 3 4. The glass composition according to claim 3, wherein:
11. 2.3≦W(SiO 2 ) -6 × W(Al 2 O 3 ) -2 × W (Li 2 O)≦10.3; 0.27≦[W(Li 2 O)-W(Al 2 O 3 )] / [W(P 2 O 5 ) + W(ZrO 2 3. The glass composition according to claim 2, wherein x = 0.
87.
12. A crystallized glass comprising the glass composition according to any one of claims 1 to 11.
13. 13. The crystallized glass according to claim 12, wherein the thickness of the crystallized glass is 0.3 to 1.5 mm.
14. The crystallized glass has a crystalline phase of Li 2 S 2 O 5 and crystalline phase LiAlSi 4 O 10 The crystallized glass according to claim 12, comprising:
15. A step S10 of weighing the glass composition according to any one of claims 1 to 11; Step S20 of mixing and melting the glass composition, then fining, homogenizing, forming, annealing, and finally cutting to obtain a base glass; and step S30 of heat-treating the base glass to obtain crystallized glass.
16. The step of heat-treating the base glass to obtain crystallized glass includes: The base glass is heated from room temperature to 530 to 570 ° C. in 20 to 60 min, and a nucleation treatment is performed for 3 h or more. The temperature is raised to 680 to 720 ° C. in 5 to 30 min, and the crystallization treatment is carried out for 3 h or more. and cooling to room temperature to obtain the crystallized glass.
17. Step S30 The base glass is heated from room temperature to 510 to 540 ° C. in 20 to 60 min, and a first nucleation treatment is performed for 3 to 8 h. The temperature is raised to 580-610 ° C. in 5-30 min, and a second nucleation treatment is performed for 3-8 h. The temperature is raised to 650 to 680 ° C. in 5 to 30 min, and a crystallization treatment is performed for 3 to 8 h. and cooling to room temperature to obtain crystallized glass.
18. After step S30, The step S40 includes pretreating the crystallized glass, placing the glass in an ion exchange bath for salt bathing, and obtaining chemically strengthened crystallized glass; Here, the ion exchange bath contains, by mass%, 20 to 40% NaNO 3 and 60-80% KNO 3 and / or The salt bath strengthening temperature is 420-500°C, and / or The method for producing crystallized glass according to claim 15, wherein the salt bath strengthening time is 3 to 8 hours.
19. 16. The method for producing crystallized glass according to claim 15, wherein in step S20, the forming method includes float forming, overflow forming, calendar forming, or slot downdraw forming.
20. An electronic display terminal comprising the crystallized glass according to claim 12 , 13 or 14 .
Citation Information
Patent Citations
Microcrystalline glass, microcrystalline glass product and manufacturing method thereof
CN113387586A
Glass-ceramic articles having improved properties and methods for making same - Patents.com
JP2021531229A
Glass-ceramics and chemically strengthened glass
JP6962512B1
Colored glass-ceramics having petalite and lithium silicate structures
US20200377404A1
